What constitutes discovery? An analysis of published interviews with fiction writers and biomedical scientists. Issue 2 (3rd April 2021) - Neave, Lucy
ABSTRACT: Literary texts reveal aspects of lived experience, historical reality and subjectivity. In Uses of Literature, Rita Felski (2008) argues that they therefore take part in practices of knowing. In the following paper, writers' recognition of moments of discovery as described in The Paris Review Interviews is contrasted with biomedical scientists' discussions of their salient discoveries in interviews from the Australian Academy of Science's website. While writing in the biomedical sciences has long been assumed to consist of 'writing up' results established in a laboratory, some research into scientific writing suggests that the process of writing itself clarifies scientists' thinking. The following paper compares interviews with writers and interviews with scientists using an online text analysis tool, Voyant. It asks how the conceptualisation of discoveries made by biomedical scientists differs from or aligns with notions of discovery among fiction writers, and what role the interview process plays in revealing how writers and scientists write. Long-held assumptions about writers' and scientists' practices affect approaches by interviewers to their subjects, yet analysis of existing interviews demonstrates how discoveries emerge in the fiction writing process; in contrast, interview questions asked of scientists likely obscure the role of writing in their work.